Reliability performance of wireless sensor network for civil infrastructure – Part I: Experimental analysis - Jang, Won-Suk; Kim, Du Yon; Skibniewski, Mirosław J (Journal of Civil Engineering and Management, 2015)
Ubiquitous computing has changed the shape of the construction industry by providing a tool of automated sensing and monitoring the construction events using wireless sensor networks (WSNs). On the other hand, wireless signals are vulnerable to a range of environmental factors, such as obstructions from built structures, construction materials and equipment. Moreover, attenuation of the signal performance from the obstructions might reduce the reliability of the WSN performance for possible applications to civil infrastructure. This paper reports the experimental findings by simulating detailed obstruction environments using major construction materials to analyze the performance reliability of wireless communication. The T-R separation distance, construction materials, and their thickness have been identified as potential attenuation components, which were also analyzed quantitatively using the path loss exponent, attenuation index and cumulative beta distribution. The results from this research are expected help general civil engineers evaluate the performance of WSNs in the applications of civil infrastructure.First published online: 09 Jul 2015